A detailed review on heat transfer rate, supercooling, thermal stability and reliability of nanoparticle dispersed organic phase change material for low-temperature applications. (June 2020) - Eanest Jebasingh, B.; Valan Arasu, A.
Abstract: Recent days, the thermal energy storage (TES) is considered as a promising technology to meet the future energy demands. Thermal energy storage based on phase change material (PCM) as energy storage material due to their low cost and high storage capacity at isothermal condition. Nanoparticle dispersed in Phase Change Material (NDPCM) improves the thermal performance of base PCM by enhancing heat transfer rate during storage as well as retrieval time as demonstrated by several researchers. However, few drawbacks like thermal stability and reliability hinder their practical application at an industrial scale. The important feature of this review was that it analyses both the scientific reasons behind the increase or decrease on heat transfer rate, thermal stability, supercooling, thermal reliability and viscosity on base PCM due to the dispersion of nanoparticles as well as supporting materials into the PCM matrix and the impact of influencing parameters like size, shape, material of the nanoparticles on the thermal properties of PCM between the operating temperature range of 20–37 °C as required in low temperature applications. The reported research works ascertain that the heat transfer rate and thermal reliability of NDPCM based thermal storage system are improved and thermal stability of NDPCM is decreased by the addition of nanoparticles. It should be noted that carbon based nanoparticle has some noteworthy effects on thermal property of PCM than metal or metal oxide nanoparticles. Highlights: Dispersion of nanoparticles in organic PCM (NDPCM) in the temperature range of 20–37 °C are reviewed. Impacts of dispersion of nanoparticles on heat transfer and supercooling, of NDPCM are analysed. Impacts of dispersion of nanoparticles on thermal stability and reliability of NDPCM are examined. Existing challenges and future research directions are suggested in this article.